Is There An Association Between Kisspeptin Levels And Gestational Diabetes Mellitus? - Arslan, Emine; Gorkem, Umit; Togrul, Cihan (Gynecology Obstetrics & Reproductive Medicine, 2020)
Objective: To find out the relationship of maternal serum levels of kisspeptin with gestational diabetes mellitus status. Study Design: A total of 158 pregnant women between 24 and 28 weeks of gestation were divided into two groups according to gestational diabetes mellitus status: (i) Pregnant women with gestational diabetes mellitus (gestational diabetes mellitus group, n=76) and (ii) Healthy pregnant women (control group, n=82). Maternal serum concentrations of kisspeptin, insulin, and homeostasis model assessment-insulin resistance were assessed. Results: In both groups, there were no difference in terms of age and gestational age (p=0.058 and p=0.820, respectively). The median of body mass indices of both groups at 24 to 28 weeks of gestation were statistically similar (p=0.062). The serum concentrations of kisspeptin did not demonstrate significant differences between the gestational diabetes mellitus and control groups (p=0.28). There was a significant difference in terms of serum level of insulin and homeostasis model assessment-insulin resistance between the gestational diabetes mellitus and control groups (p<0.001). Conclusion: No differences were found in serum kisspeptin levels between pregnant women with GDM and healthy pregnant women. Further prospective studies will be essential to elucidate the contribution of kisspeptin to gestational diabetes mellitus.